Peranakan Imageries in Malaysian and Singaporean Modern Art, 1980s-2017: Between Gendered Representations and Modern Expressions - Abdullah, Sarena (Universiti Sains Malaysia, 2019)
The revival of interest in the Peranakan community in the past few decades has largely concentrated on the cultural imagery of the Nyonya lifestyle rather than political narratives of the Straits Chinese of the early twentieth century. In particular, the hybrid elements of Nyonya culture, including Peranakan kebaya, jewellery, porcelain, embroidery, cuisine and lavish weddings, have been portrayed in books, museum exhibits, tourism brochures and the popular media as unique examples of cultural mixing that promote multi ethnic harmony and can attract tourists to the region (Worden 2003; Hardwick 2008; Teoh 2015). A similar phenomenon can be seen in the modern art world. Visual art showcasing the Nyonya in her traditional costumes and engaging in domestic activities has been exhibited in established art institutions and commercial galleries and sold commercially. Some examples include Redza Piyadasa's Malaysian series produced in the 1980s, Martin Loh's Naive Images of Days Gone By in 1992 and other exhibitions at the Substation Gallery in Singapore in the 1990s. In 1998 Sylvia Lee Goh had her first solo exhibition at the Malaysian National Art Gallery entitled Two Decades of Art 'From the Heart'1978-1998